Adolescent self‐harm with and without suicidality: cross‐sectional and longitudinal analyses of a Swedish regional register. (12th September 2018) - Bjureberg, Johan; Ohlis, Anna; Ljótsson, Brjánn; D'Onofrio, Brian M.; Hedman‐Lagerlöf, Erik; Jokinen, Jussi; Sahlin, Hanna; Lichtenstein, Paul; Cederlöf, Martin; Hellner, Clara
Abstract : Background: Self‐harm is common and there is a need for studies that investigate the relevance of this behavior in clinical samples to inform risk assessment and treatment. The objectives in the current studies were to compare clinical and psychosocial correlates and subsequent adverse outcomes in youth who present to child and adolescent mental health services (CAMHS) with self‐harm only (SH), self‐harm with suicidality (SH+SU), with those without any indication of SH or SH+SU. Methods: We conducted a case–control study and a longitudinal cohort study using data from a regional clinical care register, and Swedish national registers. The case–control study included all patients (5–17 years) between 2011 and 2015 ( N  = 25, 161). SH and SH+SU cases were compared with controls (patients without SH) regarding a range of correlates. The longitudinal study included former CAMHS patients ( N  = 6, 120) who were followed for a median time of 2.8 years after termination of CAMHS contact regarding outcomes such as clinical care consumption, social welfare recipiency, and crime conviction. Results: In the case–control study, both the SH and SH+SU groups received more clinical care, had lower global functioning, and higher odds of having mental disorders compared to controls. In most comparisons, the SH+SU group had more problems than the SH group. In the longitudinal study, the same pattern emerged for most outcomes; for example, the adjusted hazard ratio for recurrent care due to self‐harm was 23.1 (95% confidence interval [CI], 17.0–31.4) in the SH+SU group compared to 3.9 (95% CI, 2.3–6.7) in the SH group. Conclusions: Adolescent patients presenting with self‐harm have higher risks for adverse outcomes than patients without self‐harm. Suicidality in addition to self‐harm is associated with more severe outcomes, importantly recurrent episodes of care for self‐harm.